2014
DOI: 10.1002/prep.201300134
|View full text |Cite
|
Sign up to set email alerts
|

Condensed Phase Behavior in the Combustion of Ammonium Dinitramide

Abstract: This paper reports on the thermal and combustion behaviors of ammonium dinitramide (ADN). The thermal behavior is measured by a pressure thermogravimetric analysis (TGA) at pressures below 8 MPa. The burning rates of pure ADN and ADN/ammonium nitrate (AN) mixtures are measured in the range 0.2-12 MPa, and the burning temperature profiles are obtained using thermocouples with diameters of 5 and 25 mm. This report mainly focuses on the condensed-phase behavior in the vicinity of a burning sur-face. The temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Fujisato et al . clarified that the decomposition of ADN and the dissociation of AN proceed on the condensed phase of ADN combustion to generate bubbles of gaseous decomposition products . For ADN‐EILPs, bubbles were observed on the combustion surface during strand burner tests .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fujisato et al . clarified that the decomposition of ADN and the dissociation of AN proceed on the condensed phase of ADN combustion to generate bubbles of gaseous decomposition products . For ADN‐EILPs, bubbles were observed on the combustion surface during strand burner tests .…”
Section: Resultsmentioning
confidence: 99%
“…The inefficient heating of AMU631 at I CW = 5.70 W was explained considering the condensed phase reactions of highly energetic materials (HEMs) such as hydroxylammonium nitrate (HAN) and ADN [10][11][12][13][14][15].…”
Section: Mechanism Of Ignition Delay Upon Cw Laser Heatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the gas-phase decomposition mechanism, ADN in the solid-state or molten-state decomposes directly without sublimation, following the condensed-phase decomposition mechanism. [63][64][65] The detailed decomposition steps are shown in eqn ( 5)-( 14). Similarly, this mechanism also includes two competitive pathways.…”
Section: Condensed-phase Decomposition Mechanism Of Adnmentioning
confidence: 99%
“…4,5) Over the past four decades, significant research has been conducted to gain an understanding of the combustion wave structure and burning rate characteristics of ADN. Extensive experimental studies [6][7][8] and theoretical modeling [9][10][11] have been reported over a broad range of operating conditions. Recently, there have been some studies concerning the gas phase reactions and flame structure during ADN combustion, based on elemental reaction mechanism models in the gas phase.…”
Section: Introductionmentioning
confidence: 99%